Hubungan Efikasi Diri dengan Tekanan Darah Lansia di Wilayah Kerja Puskesmas Rawat Inap Negara Ratu Kabupaten Lampung Utara Tahun 2023 - Emilda, Reca; Wijayanto, Wisnu Probo; Sutrsino, Sutrsino; Kameliawati, Feri (Journal of Nursing Invention, 2024)
Background: Self-efficacy or one's confidence in maintaining a lifestyle in an effort to control blood pressure, especially in the elderly, is needed because many elderly people experience hypertension. The incidence of hypertension in the population aged 55-64 years was 29.97%, aged 65-74 years was 36.47% and aged > 75 years was 37.89%. Complications that occur in people with hypertension can be controlled with non-pharmacological therapy, namely lifestyle modification. High and low self-efficacy may influence lifestyle in people with hypertension Objective: The purpose of the study was to determine the relationship between self-efficacy and blood pressure of elderly people in the working area of Ratu State Inpatient Health Center Method: Type of quantitative research with a cross-sectional approach. The population in this study was composed of 212 elderly respondents in the Negara Ratu Inpatient Health Center Work Area, with a sample size of 139 taken by purposive sampling. Data collection used questionnaires and univariate and bivariate data analysis using the gamma test Result: The research results showed that as many as 85 (61.2%) respondents had poor self-efficacy and as many as 92 (66.2%) respondents had hypertension. There is a relationship between self-efficacy and blood pressure in the elderly in the Ratu Inpatient Health Center Work Area with a p-value of 0.001 Conclusion: Self-efficacy has been proven to have a relationship with blood pressure in the elderly